Ayurveda Management of Schizophrenia – A Case Report - M, Rinisha; K, Satheesh (International Research Journal of Ayurveda & Yoga, 2024)
Introduction- Schizophrenia is a complex, chronic mental health disorder characterized by an array of symptoms, including delusions, hallucinations, disorganized speech or behavior and impaired cognitive ability. Schizophrenia is a lifelong condition, but treatment can help manage the symptoms. Case description- A 28 year old female presented in the OPD with headache, disturbed sleep, increased anger and feeling sadness, more in the evening, since 5 months. Detailed interrogation with her mother revealed that she had irritability, increased anger, disturbed sleep and impulsivity. On mental status examination, she was found to have restricted mood and affect in addition to somatic passivity. The case was diagnosed as Schizophrenia, based on the diagnostic criteria mentioned in International Classification of Diseases 10th revision. As per the Ayurveda clinical examination, the case can be considered as Sannipathika Unmaada with PittaVata predominance. Management - The case was managed in the Inpatient department. Internal medicines were given to address the symptoms along with procedures like takrapana followed by uttamamatra snehapana, abhyanga ushmasweda and virechana. Thereafter Nasya, Thalam, Sirodhara And Dhoopana was done. Yoga and pranayama along with Smriti meditation was also done. Result Significant improvement were noted in Positive and Negative Syndrome Scale (PANSS) score after treatment.